Industrialisasi Sebagai Kekuatan Politik Negara - Kustiawan Kustiawan; Syaihidina Hefir; Zhahara Dwi Amanda; Ajeng Aprianingsih; Nana Amelia Serikat (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Industrialization has helped the economic growth and progress of many countries, but it is still understood about its effects on government, power structures, and social relations. The study investigates the impact of industrialization on these three components, with particular emphasis on Indonesia. Government has changed significantly as a result of industrialization, which has played an important role in driving industrial growth. To attract foreign investment, improve infrastructure, and improve the business environment, governments have implemented several policies, but there are concerns about their ability to oversee industry and protect the interests of local communities. In addition, the power structure has undergone significant shifts, with the emergence of new social classes and the consolidation of power among certain classes. The industrial sector has also created new opportunities for social mobility, but has also exacerbated economic and social disparities. To solve this problem, this study suggests that the distribution of wealth and power must be fairer. Industrialization, along with increased urbanization and urban growth, has had a significant impact on social relations. The study investigates how industrialization has affected social relationships, including its impact on family structures, community networks, and social identities. So, Indonesian government, power structure, and social relations are heavily influenced by industrialization. Although it has produced significant economic gains, it has also created new problems and differences. This research suggests that a deeper understanding of the impact of industrialization is vital, as are the policies needed to address the social and economic impacts of industrialisation.